First recording of the non-native species Beroe ovata Mayer 1912 in the Aegean Sea - SHIGANOVA, T.A.; CHRISTOU, E.D.; SIOKOU, I. (Mediterranean Marine Science, 2007)
A new alien species Beroe ovata Mayer 1912 was recorded in the Aegean Sea. It is most likely that this species spread on the currents from the Black Sea. Beroe ovata is also alien to the Black Sea, where it was introduced in ballast waters from the Atlantic coastal area of the northern America. The species is established in the Black Sea and has decreased the population of another invaderMnemiopsis leidyi, which has favoured the recovery of the Black Sea ecosystem.We compare a new 1 species with the native species fam. Beroidae from the Mediterranean and predict its role in the ecosystem of the Aegean Sea using the Black Sea experience.